SKILLS FOR THE FORMATION OF A HEALTHCARE CULTURE IN PRIMARY SCHOOL STUDENTS - Otabek Shanazarov (Proximus Journal Publishing, 2025)
The development of a healthcare culture among primary school students is a fundamental component of modern education, especially in the context of Uzbekistan’s ongoing reforms in the field of child development and public health. Building a healthcare culture involves forming knowledge, values, habits, and behavioral patterns that support a healthy lifestyle from an early age. This paper examines the necessary skills that primary school students should develop in order to internalize and practice healthcare values, and explores how educators can effectively guide this process through structured methodologies, appropriate curriculum integration, and supportive learning environments. The research emphasizes the importance of life skills such as personal hygiene, emotional self-regulation, physical activity, and nutritional awareness as core components of a healthcare culture. Drawing on both national experience and international models, the study proposes a set of pedagogical strategies aimed at equipping students with practical, sustainable skills that will serve them throughout life. Findings demonstrate the necessity of systematic teacher training, school-family cooperation, and the use of engaging, child-centered teaching methods. The results provide actionable insights for curriculum developers, policymakers, and educators seeking to foster a strong foundation of healthcare awareness and responsibility among children
Keywords: healthcare culture; primary education; personal hygiene